Valuation of impacts in cost benefit analysis - S., Intan Syafinaz; Juni, Muhamad Hanafiah; Ibrahim, Faisal; Manaf, Rosliza Abdul (Community Health Society Malaysia, 2017)
Background: Despite being a very useful tool in programme evaluation, CBA struggles from the problems of valuating a diverse range of impacts from a program or intervention into monetary terms. Objectives: To review the methods that had been used in the valuation of impacts for CBA including the recommendations related to the valuation as well as the advantages and disadvantages of each method. Methodology: This is a review of literatures on methods for the valuation of impacts for CBA using major healthcare databases such as PubMed, CINAHL and Google Scholar. Also performed are hand searching of relevant articles, health reports, and papers issued by government bodies and international health organizations.Result and Discussion: Among the approaches that has generally been suggested for the valuation of impacts are; the human capital approach, revealed preferences and the contingent valuation method. The human capital approach is simple to operationalize but there are several economic and ethical disadvantages that reduces its applicability. The revealed preference approach is mostly applicable in the labour market, where wage premiums are offered to workers to accept more risky jobs. But besides safety, there are also a number of other factors that affect wages which may influence the result of the study. The contingent valuation method uses surveys in the valuation of its impacts but as this method involves hypothetical data, what people say they would pay might not necessarily be the amount that they would really pay in an actual situation. Conclusion: All three methods of valuation of impacts have its equal share of strengths and limitations, thus the decision to choose between the three methods will be a matter of situation, study objectives and preferences.